Infant Bladder Rhabdomyosarcoma in a Shared-Care Centre in Ghana: Case Report and Review of the Literature - Yenli, Edwin M.T.; Bimpong, Kingsley A; Salifu, Nihad; Kwarteng, Peter G.; Cheyuo, Ernest K.; Fuseini, Yaninga H.; Anyekase, Dieu-Donnee; Akorli, Emmanuel; Der, Edmund (International Journal of Innovative Research in Medical Science, 2021)
Rhabdomyosarcoma is a fairly common soft tissue sarcoma among children. Genitourinary rhabdomyosarcoma accounts for one tenth of rhabdomyosarcomas in the West African sub-region. However, its occurrence and management are yet to be reported in our resource limited study setting. Care of such patients could be a daunting task. A comprehensive paediatric oncology service should be advocated to optimize the chances of survival. A seven-month old boy was referred to our facility on account of posterior urethral valve. A week’s complaint of crying on micturition, with associated passage of scanty urine and irritability, although he was apparently well since birth with no urinary complaints. A suprapubic mass was palpated on abdominal examination. Digital rectal examination revealed a nodular pelvic mass. Open cystostomy done and histopathology showed embryonal rhabdomyosarcoma of the urinary bladder. Chemotherapy was commenced on a modified Malignant Mesenchymal Tumour protocol of the International Society of Paediatric Oncology group. The mass was reduced by a third after six cycles of chemotherapy. In resource limited settings, the management of paediatric genitourinary rhabdomyosarcoma, using multidisciplinary and multimodal approach to include the hub for comprehensive paediatric oncology services should be advocated to optimize chances of survival.